ENHANCING WRITING SKILLS : A STUDY OF THE GROUP RESUME METHOD WITH EFL LEARNERS - Hanifah Paradipta Siregar; Bahruddin Bahruddin; Suhartina Suhartina; Petrus Jacob Pattiasina; Ferawaty Syam; Asmaul Husna (PT. Jurnal Center Indonesia Publisher, 2026)
This study aimed to examine the effect of the group résumé method on tenth-grade students’ ability to write recount texts at SMA Negeri 6 Padangsidimpuan. Specific objectives were to describe students’ writing ability before and after implementing the group résumé method and to determine whether the method produced a significant improvement. The population consisted of 124 tenth-grade students, and a systematic sampling procedure yielded a sample of 27 students. The study used an experimental design; data were collected with observation sheets and writing tests. The mean score after applying the group résumé method was 3.5, which falls into the “Very Good” category according to the study’s scoring criteria. A t-test was used to analyze the results: tcomputed = 6.73, while ttable = 2.06. Because ttest> ttable, the findings indicate that the group résumé method had a statistically significant positive effect on students’ recount writing ability.